2021
DOI: 10.3390/antibiotics10101147
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Pharmacist-Led Brief Educational Intervention for Adherence to the Antibiotics for Lower Respiratory Tract Infections (EATSA) in Post-Conflict Rural Areas of Pakistan: Study Protocol for a Randomized Controlled Trial

Abstract: Globally, lower respiratory infections (LRTIs) are one of the most common infectious diseases whichaffect majority of the population and as a result of inappropriate antibiotics practices lead to antibiotic resistance (AR). An individual randomized control trial will be conducted in the post-conflict areas of Swat, Pakistan, through a random sampling method. Patients aged > 18 years will be recruited from five community pharmacies and assigned to equally sized groups to receive either pharmacist-led educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…The current study is part of the main trial which contributes baseline data to the registered protocol (ChiCTR2000040453) and is a scheduled phase of the research project. The results that have been presented are following the EATSA protocol and serve as a foundation for the beginning of the main trial ( 27 ).…”
Section: Methodsmentioning
confidence: 99%
“…The current study is part of the main trial which contributes baseline data to the registered protocol (ChiCTR2000040453) and is a scheduled phase of the research project. The results that have been presented are following the EATSA protocol and serve as a foundation for the beginning of the main trial ( 27 ).…”
Section: Methodsmentioning
confidence: 99%
“…Antibiotics are considered as life-saving drugs; although the 19th century was dubbed the “Golden Era” as a result of its discovery, the golden period did not last long due to the rise of various resistant infections ( Akhund et al, 2019 ). ABR is a long-standing problem ( Khan and Fang, 2021 ). ABR has drastically expanded in the twenty-first century and is primarily attributed to irrational prescription and incorrect usage.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review concluded that educational intervention concomitant with other antimicrobial stewardship interventions introduced by pharmacists produced beneficial outcomes and reduced the duration of antimicrobial therapy ( Monmaturapoj et al, 2021 ). However, limited literature is available concerning educational intervention led by pharmacists in Pakistan ( Butt et al, 2019 ; Khan and Fang, 2021 ). Moreover, literary resources covering secondary care facilities concerning ASP interventions and implementation are also scarce ( Rupali and Kumar, 2022 ).…”
Section: Introductionmentioning
confidence: 99%